Roof Bolting Practice in the Collieries of Australian Iron and Steel Pty. Ltd. (The Australasian Institute of Mining and Metallurgy, 1961)
Present roof bolting practices in the collieries of Australian Iron and Steel Pty. Ltd. are outlined. Roof support has been improved since introducing roof bolts and it is hoped to increase the reliability of the bolts still further.Expansion-shell, and split and wedge roof bolts five to eight feet long are placed by "Atlas Falcon" and "Fletcher" roof bolters. Both anchorage and tightening have presented some problems.Good panel supervision is required if systematic roof bolting is to be properly co-ordinated with coal production without unnecessary delay to either. Successful roof bolting can only be the product of conscientious men and supervisors who are all convinced of its value. A rigid operational code should be established early and maintained.INTRODUCTIONRoof bolting is a method of support which is permanent and reduces or eliminates the need for other support; The method was pioneered in America and was first experimentally investigated in Australian collieries at Elrington in 1949 (McKensey, 1953). Pneumatic installation methods were employed. Subsequently, a method of using standard hand-held electric coal drills was developed at John Darling Colliery (Horseman, 1954). Pneumatic roof bolting equipment was first operated in the collieries of Australian Ironand Steel Pty. Ltd (A.I. &. S.) in 1951. Since then various hydraulically operated mobile machines have been installed in Australian collieries and these, together with improved pneumatic equipment, form the two present basic methods of placing ,roof bolts. Roof bolt anchorage is achieved by either split and wedge or expansion-shell bolts.The two broad types of roof bolting are 1. consolidation of strata, and 2. suspension support.